2007
DOI: 10.1371/journal.pone.0000933
|View full text |Cite
|
Sign up to set email alerts
|

Differential Association between HERG and KCNE1 or KCNE2

Abstract: The small proteins encoded by KCNE1 and KCNE2 have both been proposed as accessory subunits for the HERG channel. Here we report our investigation into the cell biology of the KCNE-HERG interaction. In a co-expression system, KCNE1 was more readily co-precipitated with co-expressed HERG than was KCNE2. When forward protein trafficking was prevented (either by Brefeldin A or engineering an ER-retention/retrieval signal onto KCNE cDNA) the intracellular abundance of KCNE2 and its association with HERG markedly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 63 publications
(74 reference statements)
8
36
0
Order By: Relevance
“…Thus, KCNE1 and KCNE2 associate with Kv1.5, and experiments with kcne2 null mice suggest that associations with Kv1.5 and Kv4.2, but not with Kv1.4 and Kv4.3, recapitulate cardiac I Kslow and I to,f (transient outward fast) currents Roepke et al, 2008 associations are crucial for KCNE1 expression at the plasma membrane (Chandrasekhar et al, 2006). In fact, KCNE1 shows greater ER retention than KCNE2 and this determines Kv11.1 association (Um and McDonald, 2007). KCNE4 also shows more ER retention than KCNE2.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, KCNE1 and KCNE2 associate with Kv1.5, and experiments with kcne2 null mice suggest that associations with Kv1.5 and Kv4.2, but not with Kv1.4 and Kv4.3, recapitulate cardiac I Kslow and I to,f (transient outward fast) currents Roepke et al, 2008 associations are crucial for KCNE1 expression at the plasma membrane (Chandrasekhar et al, 2006). In fact, KCNE1 shows greater ER retention than KCNE2 and this determines Kv11.1 association (Um and McDonald, 2007). KCNE4 also shows more ER retention than KCNE2.…”
Section: Discussionmentioning
confidence: 94%
“…3C, indicated that both proteins mostly share the same location. KCNE peptides are targeted to the cell surface with different efficiencies (Um and McDonald, 2007;Jiang et al, 2009). In this context, KCNE2 (Fig.…”
Section: Kcne4 Modifies Kv13 Gating and Traffickingmentioning
confidence: 99%
“…1-4 It is also shown that the KCNE1 subunit more efficiently assembles with the KCNH2 subunit than the KCNE2 subunit does, and this affects KCNH2 channel trafficking. 23 The KCNE1(38G) subunit is shown to augment KCNH2 and KCNQ1 channel currents, and this augmentation might contribute to maintaining normal channel function in cardiomyocytes. 1- 4 Our results indicate that the KCNH2 channel current augmentation effect of the KCNE1(38S) subunit is weaker than that of the KCNE1(38G) subunit.…”
Section: Kcnq1 Channel Kineticsmentioning
confidence: 99%
“…15,16 Surprisingly, KCNE2 is also thought to be secreted from the cell under some circumstances; 14 whether this is solely an in vitro phenomenon or one with physiological relevance that occurs in vivo, remains to be understood.…”
Section: Overview Of the Influence Of Kcne2mentioning
confidence: 99%
“…12,14,[71][72][73][74] In adult canine ventricular tissue, KCNE2 and cERG are colocalized in cholesterol and sphingolipid-enriched membrane fractions. 75 hERG (and ERG from other mammals) is unusual in that it is part of the S4 superfamily of voltage-gated ion www.landesbioscience.com Channelschannels that includes the Kv a subunits, but it exhibits inward rectification similar to the Kir subunits.…”
Section: Kcne2 In Cardiac Myocytes: Ventricular Repolarizationmentioning
confidence: 99%